2009
DOI: 10.1093/annonc/mdp015
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative chemoradiation in potentially resectable pancreatic adenocarcinoma: feasibility, treatment effect evaluation and prognostic factors, analysis of the SFRO-FFCD 9704 trial and literature review

Abstract: This proposed preoperative scheme is feasible, does not prevent successful surgery, and provides antitumoral effect associated with major histopathological response in 50% of patients and a high R0 resection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 50 publications
2
50
0
8
Order By: Relevance
“…It is estimated to be responsible for more than a quarter of a million deaths and be the fifth leading cause of cancer death in worldwide (Epstein et al, 2012). The prognosis is extremely poor, with 5-year survival rate of less than 5% even with the surgical and chemotherapy intervention (Le Scodan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated to be responsible for more than a quarter of a million deaths and be the fifth leading cause of cancer death in worldwide (Epstein et al, 2012). The prognosis is extremely poor, with 5-year survival rate of less than 5% even with the surgical and chemotherapy intervention (Le Scodan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Reszekábilis esetben neoadjuváns kezelésként kemoirradiáció (esetleg indukciós kemoterápiát követően) klinikai vizsgálat keretében folytatható, standard kezelési elv egyelőre nincs [32]. "Borderline" reszekábilis esetben kemoirradiációs kezeléssel "downsizing" érhető el.…”
Section: Sugárterápia 81unclassified
“…No data on os were reported. Another study of 41 patients treated with neoadjuvant chemoradiation using 5-fluorouracil and cisplatin reported that only 27 patients were able to complete treatment 27 . A major response was detected in 50% of specimens, with 1 complete response.…”
Section: Neoadjuvant Therapy In Locally Advanced Primary Unresectablementioning
confidence: 99%